The Role of Viral Marketing in Mediating the Relationship between Brand Awareness and Product Quality on Purchase Decisions - Nurul Septya Magisa; Iswanto; Ana Yuliana; Sulasti (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to analyze the impact of brand awareness and product quality on purchasing decisions, with viral marketing as a mediating variable for Mixue products in Pontianak. The method used is quantitative, with random sampling. The sample consists of 100 respondents. Secondary data collection was conducted through websites such as www.MomentumWorks.com, portaltebo.id, and Pergikuliner.com. Data analysis includes descriptive statistics, outer model, inner model, and specific indirect effects. The tool used is SmartPLS 3. The results of the study show that brand awareness has a positive but not significant effect on purchasing decisions, while product quality has a positive and significant effect on purchasing decisions. Brand awareness has a positive and significant effect on viral marketing, product quality has a positive and significant effect on viral marketing, and viral marketing has a positive and significant effect on purchasing decisions. Brand awareness has a positive and significant effect on purchasing decisions, with viral marketing acting as a mediating variable, and product quality has a positive and significant effect on purchasing decisions, with viral marketing acting as a mediating variable.